2001
DOI: 10.1016/s1074-7613(01)00153-4
|View full text |Cite
|
Sign up to set email alerts
|

Pax5/BSAP Maintains the Identity of B Cells in Late B Lymphopoiesis

Abstract: The B lineage commitment factor Pax5 (BSAP) is expressed throughout B cell development. To investigate its late function, we generated a mouse strain carrying a floxed Pax5 allele that was conditionally inactivated by CD19-cre or Mx-cre expression. Pax5 deletion resulted in the preferential loss of mature B cells, inefficient lymphoblast formation, and reduced serum IgG levels. Mature B cells radically changed their gene expression pattern in response to Pax5 inactivation. Most B cell antigens were downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
211
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(226 citation statements)
references
References 46 publications
13
211
0
2
Order By: Relevance
“…The immunohistological data are, however, conflicting. In the light of the central importance of this transcription factor for maintaining B cell identity but also for preventing B cells from embarking on any non-B lineage developmental programme (Nutt et al, 1999;Horcher et al, 2001) and also of its cellular concentration (Wallin et al, 1998), we assessed PAX-5 expression semi-quantitatively in HRS cells from primary pathological tissues. Using immunohistology, we found expression of PAX-5 in HRS cells in 13/18 (72%) cases of classical HL.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistological data are, however, conflicting. In the light of the central importance of this transcription factor for maintaining B cell identity but also for preventing B cells from embarking on any non-B lineage developmental programme (Nutt et al, 1999;Horcher et al, 2001) and also of its cellular concentration (Wallin et al, 1998), we assessed PAX-5 expression semi-quantitatively in HRS cells from primary pathological tissues. Using immunohistology, we found expression of PAX-5 in HRS cells in 13/18 (72%) cases of classical HL.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription (with random hexamers) and semiquantitative PCR were performed as described (Horcher et al 2001), using the primers shown in Supplementary Table 3. PCR products were separated on agarose gels and visualized by ethidium bromide.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…7,8 Current evidence further indicates that even committed B cells in late lymphopoiesis lose the B-cell phenotype and differentiate into various hematopoietic lineages upon inactivation of PAX5 in mouse B cells. 9 Similarly, it has been shown that different hematopoietic cell types arise from E2A-deficient hematopoietic progenitor cells 10 and recently, that committed B cells transdifferentiated into macrophages after enforced expression of CCAAT enhancer-binding protein (C/EBP) transcription factors in mouse models. 11 Thus, committed mouse B cells can be shown to be plastic by induction of remodeling of the B-cell-specific transcription factor network.…”
Section: Introductionmentioning
confidence: 99%